2018
DOI: 10.1186/s13071-018-2755-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical responses in the midgut of the silkworm, Bombyx mori, infected with Nosema bombycis

Abstract: BackgroundMicrosporidia are a group of eukaryotic intracellular parasites that infect almost all vertebrates and invertebrates. However, there is little information available of how microsporidia obtain nutrients and energy from host cells. The purpose of this study was to investigate the energy and material requirements of Nosema bombycis for the invasion procedure through analyzing the global variation of the gene expression, protein abundance, fatty acids level and ATP flux induced by the microsporidia N. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…However, few studies have examined the mechanism of host response to microsporidia infection. In previous studies, many genes were found to be induced by N. bombycis that were involved in many signal transduction pathways and are therefore key components of many cellular processes [ 19 , 41 , 42 , 43 , 44 ]. Although many genes were found to be activated by N. bombycis through a genome-wide survey in our previous study [ 41 ], these genes were determined to have different levels of background expression in subsequent work [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have examined the mechanism of host response to microsporidia infection. In previous studies, many genes were found to be induced by N. bombycis that were involved in many signal transduction pathways and are therefore key components of many cellular processes [ 19 , 41 , 42 , 43 , 44 ]. Although many genes were found to be activated by N. bombycis through a genome-wide survey in our previous study [ 41 ], these genes were determined to have different levels of background expression in subsequent work [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…B. mori is an economically important insect and a lepidopteran model for investigating gene functions. In previous studies, many genes of silkworm were found to be induced by N. bombycis that were involved in many signal transduction pathways [ 19 , 41 , 42 , 43 , 44 ]. However, there was no report that UGT was induced in silkworm, and there was also few reports that UGT was involved in the process of biological stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, shrimp infected with E. hepatopenaei have lower levels of some metabolites including carbohydrates, lipids and nucleotides (Ning et al, 2019). Silkworms infected with N. bombycis have lower levels of ATP and proteins, but the levels of several lipids are not effected (Li, Wang, Wang, & Zhou, 2018). Many metabolic pathways have also been shown to be transcriptionally upregulated in response to microsporidia infection in a variety of hosts including honeybees, silkworms, crabs, mosquitos and mammals (Desjardins et al, 2015; Ding et al, 2018; Holt, Aronstein, & Grozinger, 2013; Ma et al, 2013; Pan et al, 2018; Watson et al, 2015).…”
Section: Microsporidia Metabolismmentioning
confidence: 99%
“…It has been reported that the infection of N. bombycis resulted in up-regulation of protein degradation-related enzymes in the host midgut, including the S-phase kinase-associated protein 1, and the ubiquitin-conjugating enzyme E2G. Both of which are involved in the ubiquitin-proteasome pathway [33]. From our data, the high expression of ubiquitin was observed in N. cerana, indicating the host defense mechanism to the parasite and, therefore, triggers the protein degradation-related enzyme in N. cerana.…”
Section: Identification and Validation Of Highly Expressed N Ceranaementioning
confidence: 99%